Rosyjska depesza kondolencyjna – wzorzec gatunkowy - Białek, Ewa (Acta Polono-Ruthenica, 2018)
The aim of the study is to characterise a genre pattern of a condolence telegram in Russian. A telegram is one of many genres of diplomatic correspondence, used to give condolences and express sympathy and support on the occasion of calamities and natural disasters. The senders and receivers of telegrams are heads of state (official institutinal communication), as well as nations of both countries and people afflicted with the disaster. The study conducted on a corpus of 150 texts (50 telegrams and 100 press releases) analyses the structure and lexico-pragmatic features of texts to establish the most frequent pattern of telegram in the current textual corpus. The results of the study show that a condolence telegram is a highly conventionalized genre.